Adsorbsi Ion Cr (VI) Menggunakan Adsorben dari Limbah Padat Lumpur Aktif Industri Crumb Rubber - Salmariza, Salmariza; Mardiati, Mardiati; Mawardi, Mawardi; Sofyan, Sofyan; Ardinal, Ardinal; Purnomo, Yudo (Institution for Industrial Research and Standardization of Industry - Padang, 2016)
Research on ion Cr(VI) adsorption by using adsorbent from waste activated sludge crumb rubber industry has been done with static method (batch). The samples were fresh activated sludge solid waste of crumb rubber industry and carbonized sludge continued by KOH activated. Parameter were studied including solution pH, contact time, and initial Cr(VI) ion concentration. The results reveal that the crumb rubber industrial waste activated sludge contained high silica and alumina, there were 49.02% and 16.498% respectively, so it can be used as an adsorbent. The adsorbent exhibited good adsorption potential at pH 1 for the KOH activated sludge adsorbent and pH 2 for the fresh sludge adsorbent, with 120 minutes optimum contact time and 70 mg/L initial concentration for each adsorbent type. Adsorption data were well described by the Langmuir isotherm with maximum adsorption capacities of 2.075 mg/g and 2.232 mg/g for KOH activated sludge adsorbent and fresh sludge adsorbent respectively.ABSTRAKPenelitian tentang adsorbsi ion Cr(VI) dengan menggunakan adsorben dari limbah padat lumpur aktif industri crumb rubber telah dilakukan dengan metode statis (batch). Sampel yang digunakan adalah limbah padat lumpur aktif industri crumb rubber segar dan lumpur yang dikarbonisasi serta diaktivasi dengan KOH. Parameter yang dipelajari yaitu pH awal larutan, waktu kontak, dan konsentrasi ion Cr(VI). Hasil penelitian menunjukan bahwa limbah padat lumpur aktif industri crumb rubber mengandung silika dan alumina yang tinggi yaitu 49,0% dan 16,5%, sehingga dapat digunakan sebagai adsorben. pH optimum adsorben untuk lumpur diaktivasi yaitu pada pH 1 dan lumpur segar pada pH 2. Waktu kontak optimum yaitu 120 menit dan konsentrasi ion Cr(VI) optimum 70 mg/L untuk masing-masing adsorben. Data sesuai dengan isotherm Langmuir dengan kapasitas serapan maksimum terhadap ion Cr(VI) 2,075 mg/g untuk adsorben lumpur diaktivasi dengan KOH dan 2,232 mg/g untuk adsorben lumpur segar.